Historical Dependencies And Immediate Impacts: Germany-Russia Energy relations and Consequences of Gas Supply Disruptions Post Ukraine War - Rasool , Muhammad Shoaib; Ahmed , Dr. Ashfaq (ACADEMIA International Journal for Social Sciences, 2025)
The paper analyzes the reshaping of the Germany energy system following a full-scale Russian invasion of Ukraine in 2022, a fact that has upset decades of deep reliance on cheap Russian natural gas. Throughout its history, policy in Germany to rely on handel; Wandel Durch Handel, created considerable dependency on Russian resources supplying over 55% naturally fitting natural gas to the country as of 2021. What followed next was weaponization of energy by the Russians, which revealed very weak points and resulted in soaring prices, inflation, and industry overload in Europe. Germany responded by taking vigorous measures in terms of crisis-management, including the intensive erection of the liquid natural gas import infrastructure, the mandatory renewal of the storage, and the active energy-saving. These short-term measures were able to prevent a massive recession and black-outs. Though economically expensive in the short-run, the crises also had unintended positive consequences: a lasting reduction in gas demand, an increase in the use of renewable sources of energy (up to around 56% of electricity production by 2025), and a faster movement towards the goals of decarbonization. The episode disproved traditional energy security theories and highlighted the significance of energy versions that had been made more resilient and diversified in the context of an unstable geopolitical environment. It demonstrates the need to develop effective back-up strategies and constantly review the international energy reliance through the rapid transformation of national energy policy in response to geopolitical events.